An Ethnomathematics Exploration: The Beads Basket Craft Context for Mathematics Learning - Solfema Solfema; Rilla Gina Gunawan; Jamaris Jamna; Fenny Oktariza; Selvia Erita (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2022)
Mathematics learning will be more meaningful if it uses a cultural context. Therefore an exploration of the mathematical ideas that exist in a culture is needed. The purpose of this study was to determine the fundamental ethnomathematics activities in the process of making beads basket craft and to identify mathematical concepts in beads basket craft. This research is a qualitative research with ethnographic research. The subject of this research is the bead craftsman community in Sungai Tutung, Jambi, Indonesia. The results of this study found that the activity of making bead basket crafts involved counting (e.g. determining the number of colors of each type of bead to be used), locating (e.g. placing beads to make a pattern), measuring (e.g. measuring the length of the rope), designing (e.g. designing bead basket motif), and explaining (e.g. explain the meaning of the motif on the bead basket). In addition, it was also found the concept of geometry and the concept of social arithmetic on the beads basket craft. The researchers recommend using the results of this study in learning mathematics either through direct learning or through the use of learning media.